Trusting Others During a Pandemic: Investigating Potential Changes in Generalized Trust and Its Relationship With Pandemic-Related Experiences and Worry - Thoresen, Siri; Blix, Ines; Wentzel-Larsen, Tore; Birkeland, Marianne Skogbrott (Frontiers in Psychology, 2021)
Generalized trust, the belief that most other people can be trusted, has positive consequences for health and wellbeing. An increased sense of community is often seen in times of crisis or disaster, but it is unclear whether this is the case in the COVID-19 pandemic. The objectives of the current study were to assess whether generalized trust increased in an early pandemic phase compared to pre-pandemic levels, and whether trust was lower in individuals who felt particularly threatened or burdened in the pandemic. We compared levels of generalized trust in a population-representative Norwegian sample (n = 1041) with pre-pandemic levels from the European Social Survey (ESS). Age- and gender-adjusted expected scores were compared to observed scores, using weighted data. Secondly, we tested whether indicators of pandemic-related strain, perceived health risks, or pandemic-related worry were associated with a lower level of generalized trust. This cross-sectional study was conducted in an early opening-up phase (May, 2020). The observed levels of generalized trust in an early pandemic phase did not differ significantly from expected levels based on pre-pandemic measures. Higher trust was found among individuals who reported personal experience with the COVID-19 disease (tested positive, admitted to hospital, or lost someone to the disease). Pandemic-related worry and a high perceived health threat were both associated with a lower level of generalized trust. These results indicate that personal experiences with the COVID-19 pandemic could influence trust in others, although this link may be context-dependent. Generalized trust is considered to be an important asset in society, and promote health and well-being. As the pandemic evolves, there is a risk that we may lose, or a chance that we could gain, with potential consequences for our health.